The Influence of Work Culture Competence and Digitalization on GPAI Performance at the Ministry of Religious Affairs of Muara Enim Regency - Alfajar Nopriawan (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of the study is specifically to obtain the results of the analysis of the influence of variables HR Competence, Work Culture, Digitalization on performance partially or simultaneously. The research method uses descriptive and verifiative surveys, data collection using several methods of questionnaire techniques, interviews and documentation. This research is an associative study, where in this study there are variables that are related and can affect other variables. The population of this study was 738 Islamic Education Teachers at the Ministry of Religious Affairs of Muara Enim Regency, taken into a sample of 259 employees. Data analysis techniques in this study use a quantitative approach Data processing using SPSS 23 analysis tools. The results of this study prove that partially the competence of human resources has a positive and significant effect on the performance of Islamic Religious Education Teachers, Partially the work culture has a positive and significant effect on the performance of Islamic Religious Education Teachers, Partially digitalization has a positive and significant effect on the performance of Islamic Religious Education Teachers and simultaneously the competence of human resources, work culture and digitalization has a positive and significant effect on teacher performance Islamic religious education can be proven by the Fcalculate value of 487,964 greater than Ftabel of 3,090. The influence of the three variables is shown through the value of the coefficient of determination (R2) of 85.2% and the remaining 14.8% is influenced by other variables that were not studied in this study.